Correspondence Analysis of Contingency Tables with Subpartitions on Rows and Columns - Campo Elías Pardo (Revista Colombiana de Estadística, 2013)
We present Intra-Table Correspondence Analysis using two approaches: Correspondence Analysis with respect to a model and Weighted Principal Component Analysis. In addition, we use the relationship between Correspondence Analysis and the Log-Linear Models to provide a deeper insight into the interactions that each Correspondence Analysis describes. We develop in detail the Internal Correspondence Analysis as an Intra-Table Correspondence Analysis in two dimensions and introduce the Intra-blocks Correspondence Analysis. Moreover, we summarize the superimposed representations and give some aids to interpret the graphics associated to the subpartition structures of the table. Finally, the methods presented in this work are illustrated by their application to the standardized public test data collected from Colombian secondary education students in 2008.